Effect of Temperature and Wind on Metabolism of Northern Bobwhite in Winter - L. Wes Burger Jr.; Thomas V. Dailey; Mark R. Ryan; Eric Kurzejeski (National Quail Symposium Proceedings, 2017)
Northern bobwhite (Colinus virginianus) are widely distributed across more than half of the United States, and extending into Canada and Mexico. Within this distribution they tolerate a wide range of climatic conditions and thermal stress. Annual variation in weather can produce dramatic short-term population fluctuations, particularly in the northern portion of the distribution. To better understand effects of thermal stress on energy requirements of bobwhite, we measured roosting metabolic response to cold stress and wind speed using open respirometry in a closed-circuit wind tunnel. Oxygen consumption was measured for 8 winter-acclimated captive bobwhites at each of 8 temperatures (-15°, -10°, -5°, 0°, 5°, 10°, 20°, and 30° C) at free convection and at 3 wind speeds (0, 1, and 2 m/sec) at -15° and 0° C. Over the range of body mass we measured (201.5 ± 1.3 g, n = 64), metabolic rate varied with body mass (P < 0.001) but did not differ between sexes (P = 0.187). Mean standard metabolic rate (V02) was 3.4 ± 0.11 mL O2/minute/bird (0.0171 ± 0.0004 mL O2/ min/g) or 1.14 ± 0.04 W/bird. Below a lower critical temperature of 24.1° C, metabolic rate was linearly related to operative temperature (Te)(V02 = 7.187 - 0.1568[Te]; r2 = 0.86, P < 0.001). Metabolic rate (M–E) was linearly related to wind speed (WS) at -15° C (V02 = 9.741 + 0.4609[WS]; r2 = 0.99, P = 0.001) and 0° C (V02 = 6.713 + 0.4609[WS]; r2 = 0.99, P = 0.001). We discuss implications of these energy expenditures in the context of current research and management.
Keywords: colinus virginianus; northern bobwhite; metabolism; operative temperature; roosting; thermoregulation